ANGI — Anorexia Nervosa Genetics Initiative. (April 2020) - Bulik, Cynthia; Kennedy, Martin; Wade, Tracey
Abstract: Identification of genetic variants associated with eating disorders is underway. The Anorexia Nervosa Genetics Initiative, an initiative of the Klarman Family Foundation, has contributed to advancing the field, yielding a large-scale genome-wide association study published in Nature Genetics . Eight genetic variants significantly associated with anorexia nervosa were identified, along with patterns of genetic correlations that suggest both psychiatric and metabolic origins of this serious and life-threatening illness. This article details the role of Professor Nick Martin in contributing to this important collaboration.